Bilayer graphene nanoribbons junction with aligned holes exhibiting high ZT values. (December 2019) - Deng, Shuo; Li, Lijie; Rees, Paul
Abstract: We investigate the thermoelectric performance of armchair graphene nanoribbon (AGNR), bilayer GNRs junction (BGNRJ) and BGNRJ with holes (BGNRJ-H) by the first principles calculation with non-equilibrium Green function. It is found that the BGNRJ-H exhibits high ZT values of 9.65 and 5.55 at 300K. The reason of these significantly larger ZT values than previously observed has been calculated due to reduced thermal conductivity and enhanced electrical conductivity. The low thermal conductance comes from the van der Waals (vdW) interaction between two graphene layers. The increased electrical conductivity can be attributed to the coupling effect of aligned holes in both layers. It is found from analysis results that the electron transmission of the BGNRJ-H is much stronger than a normal BGNRJ, which gives rise to the higher electrical conductance and outstanding ZT values. Graphical abstract: Image 10131